The Effect of SBI Interest Rates, Rupiah Exchange Rates, and Inflation on Net Asset Value of Equity Mutual Funds in 2015-2018: Pengaruh Suku Bunga Sbi, Nilai Tukar Rupiah, dan Inflasi Terhadap Nilai Aktiva Bersih Reksadana Saham Tahun 2015-2018 - Fatimatus Sholihah; Wiwit Hariyanto (Academia Open, 2021)
This study aims to determine the effect of SBI interest rates, Rupiah Exchange Rates, and inflation on the net asset value of equity funds in Indonesia for the 2015-2018 period. This study uses a quantitative approach with analysis tests using multiple linear regression tests, where there are three independent variables and one dependent variable. The type of data in this study uses secondary data, in the form of data taken from the official website of Bank Indonesia. The research sample was determined by purposive sampling method with sample criteria so that it obttained 9 samples of mutual fund products over four years from 2015-2018 so as many as 36 samples of Mutual Fund Products. Based on the results of analysis technique that have been done, the results of 3 independent variables show that the exchange rate of the rupiah and inflation have no effect the net asset value of mutual fund shares, while the value of SBI interest rates effect the net asset value of stock mutual funds.